Leukemia‐derived exosomes: Bringing oncogenic signals to blood cells. Issue 10 (24th May 2019) - Sharifi, Hossein; Shafiee, Alimohammad; Molavi, Ghader; Razi, Ebrahim; Mousavi, Nousin; Sarvizadeh, Mostafa; Taghizadeh, Mohsen
Abstract: Leukemia is a cancer, which is derived from leukocytes and precursors of leukocytes in the bone marrow. A large number of pivotal biological processes are linked to leukemia pathogenesis. More insights into these mechanisms can provide a better developing pharmacological platform for patients with leukemia. Among the different players in leukemia pathogenesis, exosomes have appeared as a new biological vehicle, which can transfer oncogenic signals to blood cells. Exosomes are nano‐carriers, which enable transferring numerous cargos such as DNA fragments, RNAs, messenger RNAs, microRNAs, long noncoding RNA, and proteins. Targeting the contents of exosomes leads to the alteration of host cell behavior. Increasing evidence has indicated that leukemia‐derived exosomes could be utilized as prognostic, diagnostic, and therapeutic biomarkers for individuals suffering from leukemia. In this regard, the importance of exosomes in terms of initiation and progression of leukemia was underlined in this study.